2008
DOI: 10.1002/chem.200701429
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the Chirality of Dawson Lanthanide Polyoxometalates [α1‐LnP2W17O61]7− by Multinuclear NMR Spectroscopy

Abstract: Lanthanide complexes of the chiral Dawson phosphotungstate [alpha(1)-P(2)W(17)O(61)](10-) were used to study the formation of diastereomers with optically pure organic ligands. The present work started with the full assignment of the (183)W NMR spectra of [alpha(1)-Yb(H(2)O)(4)P(2)W(17)O(61)](7-) at different temperatures and concentrations, which allowed the structure of the dimerized form in aqueous solution to be established. Different enantiopure amino acids and phosphonic acids were screened as ligands. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…The first step toward that end was the complete assignment of the 183 W NMR signals of the lacunary compound and the Yb complex, which was based on careful analysis of the J WW coupling constants 121. Further studies showed that complexation of optically pure amino acids or phosphonic acids with [α 1 ‐Yb(OH 2 ) 4 P 2 W 17 O 61 ] 7– occurred by reversible binding of these organic ligands to Yb 122. This equilibrium had an influence on the whole POM structure, but some specific sites were more affected by the complexation and the chirality of the ligand.…”
Section: Chiral Pom Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step toward that end was the complete assignment of the 183 W NMR signals of the lacunary compound and the Yb complex, which was based on careful analysis of the J WW coupling constants 121. Further studies showed that complexation of optically pure amino acids or phosphonic acids with [α 1 ‐Yb(OH 2 ) 4 P 2 W 17 O 61 ] 7– occurred by reversible binding of these organic ligands to Yb 122. This equilibrium had an influence on the whole POM structure, but some specific sites were more affected by the complexation and the chirality of the ligand.…”
Section: Chiral Pom Structuresmentioning
confidence: 99%
“…and b) N ‐phosphonomethyl‐ L ‐proline (0.5 equiv.) 122. The chemical shift difference between the diasteromers is highlighted by the darkness of the blue color – the darker the color, the larger the chemical shift difference.…”
Section: Chiral Pom Structuresmentioning
confidence: 99%
“…For instance, Zr‐containing Keggin POM (Zr1‐K2) was found to hydrolyze less than 35% of HSA after 48 h, but the degree of hydrolysis was substantially enhanced after 192 h . However, instead of dimeric 1:2 (Zr1‐K2), the monomeric 1:1 (ZrK) form of this POM was identified as the reactive species in the hydrolysis . The Zr1‐K2 to ZrK transformation has also been reported to be assisted by the protein environment and after its formation ZrK is stabilized by electrostatic and water‐mediated hydrogen bonding interactions with the protein .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Based on our observation that a strong bond to the organic ligand coupled to additional hydrogen bonds allowed better chiral sensing of [a 1 -YbP 2 W 17 O 61 ] 7À , [10] we surmised that multiple hydrogen-bonding interactions with organic molecules could provide the key to directed chiral recognition and resolution.…”
mentioning
confidence: 98%